DATA SECURITY AND PRIVACY EDUCATION FOR THE PAGERWESI VILLAGE COMMUNITY IN THE DIGITALIZATION ERA - Frestina Bhakti Herwidyaningtyas; Andi Mulyanti Suhartini (LPPM ISTeK ICsada Bojonegoro, 2026)
In today's digital age, understanding cybersecurity and how to use it is crucial. Without adequate protection, files, personal data, and other important virtual assets could be at risk. Cybersecurity is the process of defending against cyberattacks on networks, software, and sensitive data. Technology and the internet have become integral parts of everyday life in the digital age, but the increasingly complex threats to data security and privacy in the digital environment demand a higher level of public awareness and protection. In villages, including Pagerwesi Village, public understanding of the importance of personal data security remains relatively low. Many people are not yet fully aware of the potential risks that can arise from negligence in protecting their privacy and personal data when interacting online. To support improved data security and privacy for the community, public education is being implemented. The results of the implementation of this activity indicate increased public awareness of the importance of maintaining data security and privacy, as evidenced by the significant increase in knowledge among the Pagerwesi village community after the education. For the sustainability of this program, a more inclusive approach and increased digital literacy are needed.